Uji Beberapa Ekstrak Insektisida Nabati terhadap Hama Keong Mas (Pomacea canaliculata L.) pada Tanaman Padi (Oryza sativa L.) - Lola Jenrifa; Rusli Rustam; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research was to get the best botanical insecticide extract to kill golden snail pest on paddy plant. The study arranged experimentally using Complete Randomized Design (CRD) consist of 4 treaments and 5 replications until get 20 experiment unit. Every unit was infected by 8 golden snails pest with 30 days old. The treatment was from some botanical insecticide with 10 % concentration consist of forest betel leaf extract, neem leaf extract, soursop leaf extract, and Titonia diversifolia leaf extract. The parameters those obsevered were early death (hour), lethal time 50 (hour), daily mortality (%), total mortality (%), temperature and humidity daily on study site. The result showed that neem leaf extract with 10% cocentration have the best ability and effective to control P. canaliculata with early death 15,2 hours, LT50 24,60 hours and total mortality until 95%. The soursop leaf extract and Titonia diversifolia leaf extract with 10% concentration also effective because can kill more than 80% P. canaliculata. Keyword :paddy plant, golden snail,botanical insecticide